Combined prior chronic methamphetamine treatment and gp120 expression reduce PPI in aged male but not female mice. (29th May 2022) - Jordan Walter, T.; Minassian, Arpi; Perry, William; Young, Jared W.
Highlights: Combined prior chronic METH and gp120 expression decreased PPI in aged male mice. Prior chronic METH decreased PPI in aged WT, but not gp120 female mice. Combined HIV and chronic METH may impair information processing in older men. Abstract: Methamphetamine (METH) use disorder is highly prevalent among people with HIV and is a significant public health problem. Furthermore, people with HIV are living longer and using drugs such as METH even into old age, making it important to understand the effects of METH use and aging in this population. HIV, METH, and aging negatively impact a variety of brain functions, including sensorimotor gating (i.e. - automatic, pre-conscious information processing). Sensorimotor gating is often measured using prepulse inhibition (PPI), a paradigm that can be conducted in animals, thereby allowing for preclinical studies. Little is known about how HIV, METH, and aging interact to affect PPI. The goal of this study was therefore to examine how METH affects PPI in aged gp120 mice, a mouse model of HIV. PPI was measured at 8, 14, and 22 months in male and female wild type (WT) and gp120 mice. PPI was also measured during and after METH treatment at 23–24 months. Aging was associated with decreased PPI in both sexes and genotypes. Combined prior METH treatment and gp120 expression caused the greatest reduction in PPI in aged male mice. Prior METH treatment decreased PPI in aged WT female mice, but not aged gp120 female mice. Overall, these results suggest the effects of HIV and METH on information processing seem to be influenced by age and sex. Combined HIV and METH may impair information processing in older men, but not older women.